Fast Nonradiative Decay ino‑Aminophenol - Capello, Marcela Carolina (2014)
The gas phase structure of 2-aminophenol has been investigated using UV–UV as well as IR–UV hole burning spectroscopy. The presence of a free OH vibration in the IR spectrum rules out the contribution of the cis isomer, which is expected to have an intramolecular H-bond, to the spectra. The excited state lifetimes of different vibronic levels have been measured with pump–probe picosecond experiments and are all very short (35 ± 5) ps as compared to other substituted phenols. The electronic states and active vibrational modes of the cis and trans isomers have been calculated with ab initio methods for comparison with the experimental spectra. The Franck–Condon simulation of the spectrum using the calculated ground and excited state frequencies of the trans isomer is in good agreement with the experimental one. The very short excited state lifetime of 2-aminophenol can then be explained by the strong coupling between the two first singlet excited states due to the absence of symmetry, the geometry of the trans isomer being strongly nonplanar in the excited state.